DEVELOPMENT AND EVALUATION OF PINEAPPLE (Ananas comosus [L.] Merr.) POMACE BASED EXTRUDER (2014)
In large scale juice processing, about 65% of the pineapple is extracted as juice, while the remaining 35% is the by-product called pineapple pomace. Pomace generated from juice processing constitutes a disposal problem and environmental pollution and there is no processing equipment designed in addressing this problem through the utilisation of this byproduct. This study was designed to develop a mash extruder for pineapple pomace based flour. Pineapple pomace was analysed for its proximate composition using standard methods. Pomace flour was produced by drying and grinding fresh pomace from a juice processing plant. The physical and mechanical properties of the pineapple pomace flour using cassava flour as the binder were carried out by standard methods. An experimental laboratory press was used to evaluate the extrusion point pressure at different pineapple pomace/cassava flour ratio mash (5:1, 6:1 and 7:1), the moisture content of the mash (50, 55 and 60%), die size (4, 6 and 8 mm) and temperatures (60, 80, 100 and 120oC). Response Surface Method was employed to optimise the experimental data with extrusion point pressure as the response variable while temperature, moisture content, die size and pomace ratio were the independent variables. The results obtained were used to design and test a single screw pineapple pomace extruder. Operational power, compression ratio, throughput and efficiency of the extruder were determined using standard methods. Data were analysed using ANOVA. Pineapple pomace contained 12.4% moisture content, 4.8% ash, 1.4% fat, 9.2% crude protein, 6.0% crude fibre and 66.2% carbohydrate. The static angle of repose and coefficient of friction at various combinations of pomace and cassava flours increased linearly for the entire surface with moisture content and varied with structural surface in the moisture range of 12.4 to 26.3% (d.b). The minimum value of coefficient of friction for stainless iron steel was 0.44 for pineapple pomace based flour. The extrusion point pressure was 7.51 ± iv 0.62MPa, temperature, die sizes and pomace ratio significantly (p < 0.05) influenced extrusion point pressure. Optimum conditions for the extrusion point pressure were 100oC; 4.0 mm die size, 55.0% moisture content and 6:1 pomace ratio at maximum desirability of 1:00. The power required to operate the extruder was 4.0 kW at a compression ratio of 3:1. Machine throughput was 26.1 kg/h with the extruding efficiency of 87.9%. An efficient 4.0 kW pineapple pomace based extruder has been developed, which can be used to process and conserve pineapple pomace. Keywords: Pineapple pomace-flour, Extruder-development, Point-pressure. Word count: 400